How Mentorship and Coaching Can Unlock One's Full Potential. - Davis, Natasha E. (Journal of Legal Nurse Consulting)
Committing to a mentorship or a coaching relationship, as either the coach or the mentor, is one of the most valuable decisions one can make to unlock their full potential as a leader, business owner, professional, employee, or even student. While there are distinct differences between coaching and mentoring, both serve specific purposes in the growth and development of an individual. No matter the environment or scenario -- as a legal nurse consultant, in a collegial environment, or beyond, mentorship and coaching will direct a person towards success, because it provides access to knowledge, strength, and accelerated wisdom.